The Production of Social Space and Symbolic Capital: An Ethnographic Study of Independent Coffee Shops as Arenas for the Formation of Collective Identity and the Manifestation of Urban Lifestyle in Surakarta - Eldyansyah, Andika; Muhammad Fahmi Johan Syah (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines independent coffee shops in Surakarta as social, symbolic, and cultural spaces within the context of contemporary urban society. Through participant observation and in-depth interviews with owners, baristas, and visitors, the findings reveal that independent coffee shops function far beyond mere sites of beverage consumption. The results highlight their role as articulative spaces of urban identity, arenas for the production and exchange of symbolic capital, and reflections of a modern, progressive, and reflective lifestyle. This research offers significant insights into understanding how new public spaces have become arenas for social and cultural negotiation within the rapidly developing urban landscape of Surakarta.